Persuasive Communication of Bumdes Sipadecengi in Empowering Seaweed Cultivators in Pangkep Regency - Muhammad Ischak; Firdaus Muhammad; Kamaluddin Tajibu (Jurnal Mercusuar, 2022)
The residents of Tamangapa Village in Pangkep Regency earn their livelihood primarily as fishermen, while the village itself holds significant potential for the development of natural resources, particularly seaweed. Therefore, the government's effort to establish the Village-Owned Enterprises (Bumdes) Sipadecengi aims to support seaweed cultivation in the area. The support is provided through persuasive communication. This research is conducted to understand the forms, processes, and outcomes of persuasive communication directed towards seaweed cultivators in Tamangapa Village. The research methodology involves observation, interviews, and documentation. Based on the research findings, the forms of persuasive communication by the Bumdes management in empowerment take two shapes: direct and indirect communication. The communication process consists of four stages: introduction, approaching the community, persuading, teaching, and convincing the community. The outcomes of persuasive communication in empowering seaweed cultivators in Tamangapa Village include improvement in quality, entrepreneurship, environmental awareness, and the formation of seaweed cultivation groups. The results indicate that persuasive communication has a positive influence on the community in Tamangapa Village.